BIOESTADISTICA DE LAS CARACTERISTICAS DE SECRETOR Y NO SECRETOR EN MEXICO - VELEZ OROZCO, A C; GARCIA M, VIRGEN (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1950)
A simplified technic for testing for secretion and nonsecretion of A and B antigens in saliva involved inactivation for 10-20 min at the temp of boiling water, centrifuging, and removing the supernatant fluid which may be preserved in the refrigerator s
BOL INST ESTUD MED BIOL
Keywords: BIOESTADISTICA, CARACTERISTICAS, SECRETOR, MEXICO; CIENCIAS MEDICAS; CIENCIAS CLINICAS; GENETICA CLINICA